Visceral adipose tissue area measured by computed tomography is correlated with recurrence and severity of hyperlipidemic acute pancreatitis - GUO Yan; CHEN Dongfeng; SUN Wenjing (Di-san junyi daxue xuebao, 2019)
Objective To investigate the correlation between adipose tissue distribution and the relapse of hyperlipidemic acute pancreatitis (HLAP). Methods A total of 92 patients with HLAP treated in our hospital between January, 2015 and November, 2017 were enrolled in this study. All the patients were followed up for 12 months for relapse of HLAP. The clinical data were compared between the patients with and without relapse to analyze the factors associated with HLAP recurrence. Results Forty-seven patients experienced relapse of HLAP during the follow-up and 45 did not. No significant differences were found between the patients with and without relapse in gender, age, triglyceride, cholesterol, fasting blood glucose or subcutaneous adipose tissue (SAT) area measured on CT (P>0.05), but visceral adipose tissue (VAT) area differed significantly between the patients (P < 0.05). Univariate analysis showed that VAT area was associated with HLAP recurrence. Multivariate logistic regression analysis revealed that VAT area was an independent risk factor for HLAP recurrence (OR=2.55, 95%CI: 1.18-5.54; P < 0.05). Correlation analysis between CT severity index (CTSI) and VAT area in patients with HLAP recurrence suggested that VAT area was also correlated with the severity of recurrent HLAP (P < 0.05). Conclusion VAT area as an independent risk factor of HLAP recurrence is also associated with the severity of recurrent HLAP.